Proteomics Profiling of Exosomes from Primary Mouse Osteoblasts under Proliferation versus Mineralization Conditions and Characterization of Their Uptake into Prostate Cancer Cells - Mehmet Asım Bilen; Tianhong Pan; Yu-Chen Lee; Song-Chang Lin; Guoyu Yu; Jing Pan; David H. Hawke; Bih-Fang Pan; Jody V. Vykoukal; Kavanya Gray; Robert L. Satcher; Gary E. Gallick; et al. (2017)
Osteoblasts communicate both with normal cells in the bone marrow and with tumor cells that metastasized to bone. Here we show that osteoblasts release exosomes, we termed osteosomes, which may be a novel mechanism by which osteoblasts communicate with cells in their environment. We have isolated exosomes from undifferentiated/proliferating (D0 osteosomes) and differentiated/mineralizing (D24 osteosomes) primary mouse calvarial osteoblasts. The D0 and D24 osteosomes were found to be vesicles of 130–140 nm by dynamic light scattering analysis. Proteomics profiling using tandem mass spectrometry (LC–MS/MS) identified 206 proteins in D0 osteosomes and 336 in D24 osteosomes. The proteins in osteosomes are mainly derived from the cytoplasm (∼47%) and plasma membrane (∼31%). About 69% of proteins in osteosomes are also found in Vesiclepedia, and these canonical exosomal proteins include tetraspanins and Rab family proteins. We found that there are differences in both protein content and levels in exosomes isolated from undifferentiated and differentiated osteoblasts. Among the proteins that are unique to osteosomes, 169 proteins are present in both D0 and D24 osteosomes, 37 are unique to D0, and 167 are unique to D24. Among those 169 proteins present in both D0 and D24 osteosomes, 10 proteins are likely present at higher levels in D24 than D0 osteosomes based on emPAI ratios of >5. These results suggest that osteosomes released from different cellular state of osteoblasts may mediate distinct functions. Using live-cell imaging, we measured the uptake of PKH26-labeled osteosomes into C4-2B4 and PC3-mm2 prostate cancer cells. In addition, we showed that cadherin-11, a cell adhesion molecule, plays a role in the uptake of osteosomes into PC3-mm2 cells as osteosome uptake was delayed by neutralizing antibody against cadherin-11. Together, our studies suggest that osteosomes could have a unique role in the bone microenvironment under both physiological and pathological conditions.